Reducer Abnormal Noise Analysis and Control Strategy Optimization for an Electric Vehicle Braking at Low Speed Condition - Jun Zhang; Wenbing Huang; Guowei Dou; Yongzhong Bao (Jixie chuandong)
Due to the underdamping dynamics characteristics of the electric drivetrain system， the pure electric vehicle is prone to shock noise or vehicle shudder under the transient conditions of acceleration/deceleration， taking off or cruise， which seriously reduces the vehicle driving comfort. The abnormal noise problem of a front drive pure electric vehicle under low-speed braking condition is taken as an example， and the test analysis and investigation process are systematically expounded. The potential abnormal noise mechanism and control strategy are proposed. Moreover， without modifying the hardware architecture of the transmission system， the abnormal noise is eliminated through the improvement and optimization of the motor torque zero-crossing filtering strategy and the active damping control. The actual vehicle test also verifies the effectiveness of the improved scheme， which has important engineering reference value for solving the transient vibration and noise problems.